(untitled) (Ágora Journal, 2023)
This article seeks to map the performance of the following historical figure: party doctors and their established communication with the central power via the Overseas Council. In this sense, dialogues instituted with the royal sphere of power were raised, through the said institution, intermediary of these communications. Applications and petitions of physicians who worked in the captaincy of Minas Gerais were mapped. From this survey it was possible to identify the demands and guidelines of these subjects. These agents, also known as physicists, set a certain amount to be received from city councils for their services to the local population. It is necessary, in this sense, to highlight the fact that in the mid-eighteenth century, given the lack of universities and training schools in the area of medicine in Portuguese America, these subjects needed to go to European centers, in universities such as that of Coimbra, Montpellier, Leiden, among others, to graduate. In any case, due to their exclusively intellectual training, these doctors were configured as true rarities in colonial realities, therefore, I will bring here those few found in the captaincy of Minas, and the relationships they woven with the government authorities.